Unravelling unknown cyanobacteria diversity linked with HCN production - Panou, Manthos; Gkelis, Spyros (Molecular phylogenetics and evolution, 2022)
[Display omitted] •Isolation and characterisation of cyanobacteria from different regions/habitats of Europe.•Four new species (two belonging to two new genera) inhabiting terrestrial caves.•Four new species (one new genus) from freshwater, brackish and coastal ecosystems.•First report of cyanobacteria from an anchialine cave; novel taxon Speleotes anchialus.•Widespread production of HCN; epilithic lifestyle seems to favour HCN production. Cyanobacteria are ecologically versatile microorganisms, occupying diverse habitats, from terrestrial caves to coastal shores and from brackish lakes to thermal springs. Cyanobacteria have also been linked with hydrogen cyanide (HCN), mainly for their ability to catabolize HCN by the nitrogenase enzyme. In this context, we sampled disparate environments, spanning from Canary Islands and Iceland to Estonia and Cyprus. Eighty-one (81) strains were isolated and characterised with taxonomic indices and molecular markers (16S-23S rRNA region and cpcBA region), whilst their ability to produce HCN was evaluated. This approach resulted in the description of five new genera (Speleotes, Haliplanktos, Olisthonema, Speos, and Iphianassa) and their type species (S. anchialus, H. antonyquinny, O. eestii, S. fyssassi, I. zackieohae) representing Chroococcales, Chroococcidiopsales, Oscillatoriales, Synechococcales, and Nostocales orders, respectively. We also found unique lineages inside the genera Komarekiella, Stenomitos, Cyanocohniella, and Nodularia, describing four new species (K. chia, S. pantisii, C. hyphalmyra, N. mediterannea). We report for the first time a widespread production of HCN amongst different taxa and habitats. Epilithic lifestyle, where cyanobacteria are more vulnerable to grazers, had the largest relative frequency in HCN production. In this work, we show novel cyanobacteria diversity from various habitats, including an unexplored anchialine cave, and possible correlation of cyanobacteria chemo- with species diversity, which may have implications on strategic focusing of screening programs on underexploited taxa and/or habitats.